Deep Boredom: Byung-Chul Han's Philosophical Therapy for Digital Anxiety - Ping HU (Yixue yu zhexue, 2025)
Digital anxiety is a new form of anxiety that has emerged in the digital age, with a higher anxiety index that makes traditional therapeutic methods difficult to cope with. This has made philosophical therapy a new perspective for medical reflection in the digital age. Through Byung-Chul Han's philosophical analysis of the excessive self behind digital anxiety, it is revealed that as a positive survival emotion, it neglects its connection with the negative. Therefore, we can use negative emotions such as deep boredom to achieve a transformation toward a relaxed state of existence. The philosophical treatment of anxiety in the digital age should be interconnected with psychological and pharmacological perspectives to form a closed loop that is both holistic and systematic, which can help to carry out more comprehensive and in-depth intervention and treatment of digital anxiety.